Metalinguistic awareness in L2 vocabulary acquisition: which factors influence learners' motivations of form-meaning connections?. Issue 3 (3rd July 2017) - Candry, Sarah; Deconinck, Julie; Eyckmans, June
ABSTRACT: Research has shown that prompting learners to elaborate on the appropriateness of form-meaning links can be an efficient vocabulary learning exercise (Deconinck, Boers & Eyckmans, 2017). In this paper we wish to shed more light on the mental processes that occur during this specific elaborative task by investigating the influence of individual learner variables pertaining to prior linguistic knowledge and a number of word-specific features. To this end fifty Dutch-speaking EFL learners rated the congruency they perceived between the form and meaning of 24 English words on a 6-point Likert scale. The motivation of their scores was elicited by means of a think-aloud protocol, the transcriptions of which were analysed with regard to the type of elaborations made. Vocabulary size tests and a language background questionnaire provided us with additional information about the learners. We identified five types of elaborations: cross-lexical associations, sound-symbolic associations, word-form comparisons, morphological associations, and idiosyncratic associations. The data also reveal that the individual learner variables and word-specific features examined in the present study have an influence on the number of elaborations made by the learners. Pedagogical implications and suggestions for further research are discussed.